Sustainable bioenergy production : an integrated approach - Ruppert, Hans; Kappas, M. (Martin); Ibendorf, Jens (Heidelberg : Springer, 2013)
This book focuses primarily on the advantages and implications of sustainable bioenergy production in terms of ensuring a more sustainable world despite its growing energy demands.
Keywords: Biomass energy; Renewable energy sources; Energy crops -- Environmental aspects; Agriculture and energy